Effect of rainfall and swath density on dry matter and composition change during drying of switchgrass and corn stover. (January 2017) - Khanchi, Amit; Birrell, Stuart J.
Abstract : During field drying, crops can be subjected to rainfall losses due to leaching, respiration and mechanical treatments. The objective of this study was to measure the impact of rainfall amount (8–75 mm) and crop density (0.8–2.6 (corn stover), 1 to 3.2 (switchgrass) kg [DM] m −2 ) on dry matter and composition change of corn stover (CS) and switchgrass. CS and switchgrass lost 0.3–4.7% and 0.2–2.8% as leaching loss from 8 to 75 mm of rainfall, respectively. After the incubation period of 48 h, the dry matter loss increased to 7.2–9.8% (CS) and 2.6–6.1% (switchgrass) from 8 to 75 mm of rainfall, respectively. Water soluble portion of CS and switchgrass was more severely affected than the fibre portion. Corn stover, being more exposed to rainfall in low density (LD) swaths, lost 56.7% ash content, compared to 19% in high density (HD) swaths. In CS, a significant decrease of K (10.2–63.8%) and Mg (5.6–41.7%) was observed with greater reductions in LD swaths compared to HD swaths. Similarly, a significant decrease in K (6.2–23.0%) and Mg (5.1–17%) content was observed in switchgrass but it was less prominent than CS. Highlights: Leaching loses up to 2.8% and 4.7% were observed from switchgrass and corn stover, respectively. Total dry matter loss varied from 2.6 to 6.1% (switchgrass) and 7.2 to 9.8% (corn stover) with 8 to 75 mm of rainfall. Losses from switchgrass and corn stover increased as swath density was decreased during rainfall. Fibre contents increased after rainfall with the loss of more soluble components. K and Mg content decreased significantly after the rainfall treatments from both switchgrass and corn stover.